2019
DOI: 10.1186/s13018-019-1312-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the efficacy of a transverse process bone graft with other bone grafts in the treatment of single-segment thoracic spinal tuberculosis

Abstract: Background There was a controversy about bone grafting of spinal tuberculosis treatment. The aim of this study was to compare the clinical efficacy of a new bone grafting method—transverse bone grafting (TBG)—with iliac bone grafting (IBG) and titanium mesh grafting (TMG) in the treatment of single-segment thoracic spinal tuberculosis. Material and methods TBG was undertaken in 30 patients (group A), IBG was carried out in 28 patients (group B), and TMG was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…However, problems such as subsidence, stress occlusion, and radiation opacity can affect surgical planning [14][15][16][17][18][19][20] . Although the transverse process had advantages of reducing trauma, shortening hospital stay, the bone defects caused by the lumbar spine TB are larger than these in thoracic spine which the transverse processes of lumbar spine have deeper anatomical characteristics limited by difficulty in being exposed and which the mechanical requirements of lumbar spine are higher than thoracic spine [21][22][23][24] . Therefore, this study aimed to find a new method of bone grafting to provide support and promote bone fusion to reduce the incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, problems such as subsidence, stress occlusion, and radiation opacity can affect surgical planning [14][15][16][17][18][19][20] . Although the transverse process had advantages of reducing trauma, shortening hospital stay, the bone defects caused by the lumbar spine TB are larger than these in thoracic spine which the transverse processes of lumbar spine have deeper anatomical characteristics limited by difficulty in being exposed and which the mechanical requirements of lumbar spine are higher than thoracic spine [21][22][23][24] . Therefore, this study aimed to find a new method of bone grafting to provide support and promote bone fusion to reduce the incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…First, in our study, the surgery time in minutes, blood loss, hospitalization time, hospital cost and drainage volume were 182.40 ± 23.82 min, 280.80 ± 76.82 mL, 14.05 ± 3.58 days, 74,382.00 ± 11,938.00 yuan, and 340.00 ± 167.20 mL, respectively. Compared with the iliac crest or fibula graft used in previous studies [17][18][19][20][21][22][23][24] , the use of the LSP could reduce trauma and bleeding, shorten surgical and hospitalization times, decrease postoperative drainage volumes, and reduce postoperative complication rates. The LSP are present in the surgical exposure area during the posterior approach, which can reduce bleeding and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracolumbar junction (T12-L1) is one of the main sites of metastatic musculoskeletal TB [6, 7]. Although standard anti-TB chemotherapy is the fundamental method of treating spinal TB, suitable and timely surgical intervention for thoracolumbar spinal TB patients can improve spinal stability, decompress the spinal cord and prevent further development of spinal deformity and paralysis or death [17].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that transverse process bone grafts could obtain good clinical efficacy for singlesegmental thoracic TB with an average bone graft fusion time of 5.85 months without serious complications (14). Besides, the transverse process bone graft was found superior to the iliac bone graft and titanium mesh bone graft in surgical trauma, postoperative recovery, and complications (15). Therefore, in our previous studies, both granular bone grafts and transverse process bone grafts showed satisfactory clinical results in thoracic TB surgery and thus have a good application prospect.…”
Section: Introductionmentioning
confidence: 98%